PSAK 74 Implementation and Conflict of Interest in the Digital Insurance Era - Damayanti, Mutiara; Rindhyanti, Laiza Shendy; Winarto, Thomas Alvando; Yusnaini, Yusnaini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The transformation of financial reporting architecture in the insurance industry through the implementation of PSAK 74 (IFRS 17) marks a fundamental shift from the historical cost model toward current value. However, in the digital era, this standard brings massive technological integration challenges and potential agency problems due to technical complexity and managerial subjectivity. This study aims to develop Systematic Literature Review (SLR) to identify the determinants of success and ethical barriers in the implementation of PSAK 74. Usinh the PRISMA Guildelines, 36 articles published between 2020 and 2025 were analyzed through a thematic approach. The mapping results show that 58.3% of the literature originates from reputable international journals, Indonesia becoming major reserch focus (41,6%). This indicates challenges related to IT infrastructure and human resource. Research findings reveal that financial reporting quality and transparency are the most dominant dependent variables affected by the adoption of this standard. Through the lens of agency theory, it was found that the principle-based nature of the standard provides broad discretionary space in determining actuarial assumptions such as discount rates and Contractual Service Margin (CSM), which could potentially be exploited for earnings management practices to maintain Risk-Based Capital (RBC) ratios. Meanwhile, legitimacy theory explains the tendency of insurance entities to engage in symbolic compliance to gain public recognition despite internal information asymmetry. This study concludes that the success of PSAK 74 in protecting the public interest highly depends on the transformation of IT systems into substantive internal control instruments to reduce opacity in insurance financial reporting.